2017
DOI: 10.1002/cncy.21879
|View full text |Cite
|
Sign up to set email alerts
|

The impact of noninvasive follicular thyroid neoplasm with papillary‐like nuclear features on the performance of the Afirma gene expression classifier

Abstract: BACKGROUND: A recent revision in thyroid tumor nomenclature has resulted in a change from a malignant diagnosis (noninvasive follicular variant of papillary thyroid carcinoma) to one that is nonmalignant (noninvasive follicular thyroid neoplasm with papillary-like nuclear features [NIFTP]). The objective of the current study was to evaluate the impact of this change on the performance of the Afirma gene expression classifier (GEC). METHODS: The authors retrospectively analyzed consecutive thyroid fine-needle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 41 publications
4
62
0
Order By: Relevance
“…Two of these cases had undergone preoperative molecular testing, both with GEC Suspicious results. The current use of NIFTP nomenclature appears to lower the positive predictive value (PPV) as previously published by Hang et al; they observed a reduction in PPV to identify malignancy from 23% to 13% in the FN/SFN group. Recent publication from Jug et al also noted a reduction in PPV for both the Afirma GEC and ThyroSeq v2 when accounting for nonmalignant NIFTP lesions, from 30.1% to 25.3% and 42.9% to 14.3%, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…Two of these cases had undergone preoperative molecular testing, both with GEC Suspicious results. The current use of NIFTP nomenclature appears to lower the positive predictive value (PPV) as previously published by Hang et al; they observed a reduction in PPV to identify malignancy from 23% to 13% in the FN/SFN group. Recent publication from Jug et al also noted a reduction in PPV for both the Afirma GEC and ThyroSeq v2 when accounting for nonmalignant NIFTP lesions, from 30.1% to 25.3% and 42.9% to 14.3%, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…The initial prospective validated GEC study did not consider NIFTP, and only few papers have evaluated the impact of NIFTP on the performance of GEC. The diagnostic role of the Afirma test to detect NIFTP has been controversial . As reported in different series, NIFTP is associated with suspicious Afirma GEC results .…”
Section: Niftp and Molecular Testingmentioning
confidence: 98%
“…This recent acknowledgement of the role of molecular testing formalizes their use in defining risk stratification of patients with thyroid nodules. In this review, we discuss the clinical implications of the different molecular tests in the indeterminate Bethesda categories . It is important to note that the literature to date generally supports employing a combination of morphology and molecular testing to best guide the clinical or surgical approach for patients diagnosed with indeterminate thyroid nodules (Table ).…”
Section: Molecular Test Options and Molecular Approach To Indeterminamentioning
confidence: 99%
See 1 more Smart Citation
“…Hang et al suggested that separating lesions with and without Hurthle cell features may be helpful to maximize the benefit of Afirma GEC in the latter group 19. Hang et al suggested that separating lesions with and without Hurthle cell features may be helpful to maximize the benefit of Afirma GEC in the latter group 19.…”
mentioning
confidence: 99%